2004
DOI: 10.1089/tmj.2004.10.s-54
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Psychiatrist Evaluation and Patient Symptom Report in a Jail Telepsychiatry Clinic

Abstract: The effectiveness of a jail telepsychiatry service was evaluated by comparing psychiatrist and inmate report of psychopathology. Sixty-two inmates completed a total of 107 consultations at a rural county jail via interactive televideo. The inmates completed the Symptom Rating Checklist-90-Revised (SCL-90-R), and the psychiatrist completed a Psychiatrist Evaluation Form including the Clinical Global Impression Scale-Severity Index (CGI) after each teleconsultation. Most inmates were rated mild to moderately ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 14 publications
2
40
0
1
Order By: Relevance
“…Fortunately, anecdotal reports and empirical evidence revealed the feasibility of the administration of the traditional assessment instruments using the VC medium. Preliminary and earlier studies found similar results for forensic assessments administered via both face-to-face and VC media (Lexcen, Hawk, Herrick, & Blank, 2006;Manguno-Mire et al, 2007;Nelson, Zaylor, & Cook, 2004). The findings of the studies suggest that assessment measures can be administered using VC insofar as appropriate steps are initiated to ensure semblance with the traditional assessment method.…”
Section: Testing and Assessmentsupporting
confidence: 56%
“…Fortunately, anecdotal reports and empirical evidence revealed the feasibility of the administration of the traditional assessment instruments using the VC medium. Preliminary and earlier studies found similar results for forensic assessments administered via both face-to-face and VC media (Lexcen, Hawk, Herrick, & Blank, 2006;Manguno-Mire et al, 2007;Nelson, Zaylor, & Cook, 2004). The findings of the studies suggest that assessment measures can be administered using VC insofar as appropriate steps are initiated to ensure semblance with the traditional assessment method.…”
Section: Testing and Assessmentsupporting
confidence: 56%
“…[29][30][31] In the USA, for instance, use of telemedicine started in July 1997 with pulmonary, orthopaedics, diabetic, and dermatology offerings, and currently telemedicine is a key part of an integrated and successful health care system for inmates. [31][32][33][34][35][36] In Europe this should be recommended, as problems of health and shortage of resources in prisons were described on the last report of the European Prison Observatory. [37] To review and monitor the benefits of telemedicine at national and regional level, the World Health Organization (WHO) established the Global Observatory for e Health (GOe).…”
Section: Introductionmentioning
confidence: 99%
“…Several articles addressed diagnosis or assessment studies with adult patients, including a meta-analysis (Hyler, Gangure, & Batchelder, 2005). There were four studies in forensic settings (Leonard, 2004;Lexcen, Hawk, Herrick, & Blank, 2006;Nelson, Zaylor, & Cook, 2004;Zaylor, Nelson, & Cook, 2001) (see Table 2). Like studies on treatment outcome, the assessment articles focused on patient or clinician satisfaction (Matsuura et al, 2000) and equivalence of telepsychiatric assessment to in-person assessment (Baer et al, 1995;Cullum, Weiner, Gehrmann, & Hynan, 2006;Hersh et al, 2002;Marcin et al, 2005;Shore et al, 2007;Zarate et al, 1997).…”
mentioning
confidence: 99%